Circulating extracellular vesicles as predictive biomarkers of progressive interstitial lung disease in systemic sclerosis—a prospective cohort study - Colic, J.; Pruner, I.; Damjanov, N.; Antovic, J.; Sefik-Bukilica, M.; Cerinic, M. Matucci; Antovic, A. (Frontiers in Medicine, 2025)
ObjectivesTo assess in patients with systemic sclerosis (SSc) the concentration of different subpopulations of circulating extracellular vesicles (EVs) and their association with the progression of interstitial lung disease (PF-ILD).MethodsThe prospective study included 59 SSc cases, 54% with interstitial lung disease (ILD). Plasma levels of EVs were analysed with flow cytometry and labelled as endothelial (EEVs), platelet (PEVs), leucocyte (LEVs), and EVs, expressing ICAM1, TF, or HMGB1. The presence of ILD was defined by HRCT. Lung functional tests were done every 3–6 months over a 3-year follow-up period. PF-ILD was defined as ≥10% decline of FVC % from baseline, or ≥5–9% along with a decline in DLCO of ≥15%.ResultsAt baseline, 32/59 SSc patients had ILD, with a median disease duration of 3 years, and 38% were therapy naïve. In ILD patients, increased levels of all investigated EVs were found in respect to SSc patients without ILD (p < 0.05). Therapy naïve ILD cases had altered only ICAM1 + EVs compared to treated (p < 0.05). Multivariate regression analysis (MR) showed an independent association of PEVs (OR 1.004, 95% CI 1.001–1.01) and ICAM1 + EVs (OR 1.3, 95% CI 1.1–1.5) with ILD. During the follow-up period, 12/32 ILD patients developed PF-ILD, and in this group, the levels of all explored EVs were elevated compared to those without PF-ILD (p < 0.05). In an ROC analysis, all EVs showed a good ability to identify PF-ILD patients (p < 0.05). Cox MR confirmed the independent predictive value of ICAM1 + EVs (HR 1.1, 95% CI 1.01–1.1) with SSc PF-ILD.ConclusionCirculating EV levels are increased in SSc and correlate with ILD. In particular, ICAM1 + EVs may be a novel biomarker of PF-ILD, identifying SSc patients at high risk of progression who may require early aggressive treatment. Based on our results, the role of EVs in the pathogenesis and progression of ILD should be investigated further.